Analisis Semiotik Pola Asuh Belajar Ibu Single Parent Dalam Film Drama Korea The Good Bad Mother - Putri, Okta Tri; Riyanto, Buddy; Muadz, Muadz (Solidaritas, 2024)
Film is a mass communication medium whose message is very effective in spreading. Korean dramas are one of the films that are popular with Indonesian people because of the Korean Wave or Hallyu as the spread of South Korean culture. The Good Bad Mother is a Korean drama film that depicts the learning patterns of single parents in educating their children to success. However, this parenting style has become a debate among viewers on social media. The purpose of this research is to find out and identify the true meaning of the mother's learning parenting scene single parent which is found in Korean drama films The Good Bad Mother. The method used in this research is descriptive qualitative using Roland Barthes' Semiotic theory which contains elements of denotation, connotation and myth. Thedata collection technique in this research is to examine documents in theform of parenting learning scenes in films. The result of this research is toidentify and describe scenes of single parent mothers' learning parentingpatterns using Roland Barthes' semiotic analysis in the form of denotation,connotation and myth. From the results of this research it can be concludedthat the mother's learning parenting style single parent in Korean dramasThe Good Bad Mother authoritarian who always forces children to studyand forces children to work as prosecutors but also acts firm and disciplinedaccording to Confucian teachings in South Korea. Keywords: Film, Parenting, Roland Barthes’ Semiotics